2016
DOI: 10.3390/met6120301
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical and Corrosion Properties of Friction Stir Welding High Nitrogen Martensitic Stainless Steel 30Cr15Mo1N

Abstract: High nitrogen martensitic stainless steel 30Cr15Mo1N plates were successfully welded by friction stir welding (FSW) at a tool rotation speed of 300 rpm with a welding speed of 100 mm/min, using W-Re tool. The sound joint with no significant nitrogen loss was successfully produced. Microstructure, mechanical and corrosion properties of an FSW joint were investigated. The results suggest that the grain size of the stir zone (SZ) is larger than the base metal (BM) and is much larger the case in SZ-top. Some carbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Martensitic high nitrogen stainless steel 30Cr15Mo1N with 0.44 wt % nitrogen has been developed successfully in Northeastern University using pressure metallurgy method. The microstructure, mechanical and corrosion properties of friction stir welding 30Cr15Mo1N were investigated in our previous study, and the results revealed that the weldment exhibited lower hardness and better corrosion resistance [ 24 ]. The present work aims to reveal the relationship between microstructure and corrosion behavior of 30Cr15Mo1N at different austenitizing temperatures, and promote the development and application of martensitic high nitrogen stainless steels.…”
Section: Introductionmentioning
confidence: 99%
“…Martensitic high nitrogen stainless steel 30Cr15Mo1N with 0.44 wt % nitrogen has been developed successfully in Northeastern University using pressure metallurgy method. The microstructure, mechanical and corrosion properties of friction stir welding 30Cr15Mo1N were investigated in our previous study, and the results revealed that the weldment exhibited lower hardness and better corrosion resistance [ 24 ]. The present work aims to reveal the relationship between microstructure and corrosion behavior of 30Cr15Mo1N at different austenitizing temperatures, and promote the development and application of martensitic high nitrogen stainless steels.…”
Section: Introductionmentioning
confidence: 99%
“…The chloride ion residue was decreased and resulted in a lower corrosion rate [43]. In general, the corrosion resistance of the joint is affected by precipitation and grain boundary characteristics [44]. At grain boundaries, the precipitation of the chromium carbides causes susceptibility to intergranular corrosion [45].…”
Section: Results Of Corrosion Testmentioning
confidence: 99%
“…This homogenous structure was achieved due to the proper spindle speed, welding speed and in situ heat input. The sample S4 is also acceptable, but the grain structure gained was not homogenous [47][48][49][50]. The increase in the values of parameters initially increased the joints' corrosion resistance, and later it decreased after attaining the spindle speed of 1150 rpm and welding speed of 40 mm/min.…”
Section: Macro and Microstructure Analysismentioning
confidence: 98%